2022
DOI: 10.1186/s12909-022-03512-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing simulated interviews and feedback to maximize medical students’ self-efficacy in real time

Abstract: Background Self-efficacy is crucial in improving medical students’ communication skills. This study aims to clarify where medical students’ self-efficacy is greatest following an interview with a simulated patient and subsequent feedback. Methods A total of 162 medical students (109 men, 53 women) in their fourth or fifth year at a university in Japan participated in this study. The degree of self-efficacy in medical interviewing was measured befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Equally important, Aoki et al (2022) found in research involving a total of 162 medical students, the ANOVA analysis revealed that self-efficacy contributes the highest points to optimizing student feedback in real-time. This evidence proves that self-efficacy is one of the crucial factors to improve people's communication skills, importantly in real-time interaction and it helps to assist necessary action in a given situation.…”
Section: Self-efficacymentioning
confidence: 86%
“…Equally important, Aoki et al (2022) found in research involving a total of 162 medical students, the ANOVA analysis revealed that self-efficacy contributes the highest points to optimizing student feedback in real-time. This evidence proves that self-efficacy is one of the crucial factors to improve people's communication skills, importantly in real-time interaction and it helps to assist necessary action in a given situation.…”
Section: Self-efficacymentioning
confidence: 86%
“…Akizuki et al reported that feedback obtained using electronic goniometer measurements in knee joint ROM measurement improved the measurement accuracy of students and enabled them to acquire skills 38 ) . Furthermore, Aoki et al reported that medical students’ self-efficacy increased after feedback 39 ) . These findings suggest that feedback may improve the accuracy of ROM measurements and have a positive effect on self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…13,33,[35][36][37][38] Studies have reported self-efficacy as being a predictor of various qualities in medical students including mental health and wellbeing, 39,40 self-esteem; 41 confidence, 42 and patient-centered communication skills to improve clinical outcomes. 43 The link between low self-efficacy and increased feeling of burnout has been reported among medical students. 39,44 Academic selfefficacy, proactive personality and psychological safety were also demonstrated to be important for critical thinking.…”
Section: Introductionmentioning
confidence: 99%